2004
DOI: 10.1007/s00122-004-1783-9
|View full text |Cite|
|
Sign up to set email alerts
|

A major QTL conditioning salt tolerance in S-100 soybean and descendent cultivars

Abstract: Deployment of salt tolerant cultivars is an effective approach to minimize yield loss in a saline soil. In soybean, Glycine max (L.) Merr., substantial genetic variation exists for salt response. However, breeding for salt tolerance is hampered because no economically viable screening method has been developed for practical breeding. To facilitate the development of an effective screening method for salt tolerance in soybean, the present study was conducted to determine the heritability of salt tolerance and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 31 publications
9
138
2
1
Order By: Relevance
“…Satt515, Satt212 and Satt232 were three QTLs for CFC (Hyten et al 2004; Lee et al 1996a, b, c;Mansur et al 1993), Sat_289, Satt232 and Satt156 were three QTLs for PH (Lee et al 1996a, b, c;Mansur et al 1996;Lark et al 1995), Satt156 was the QTL for both CPC and PM (SoyBase81203828 and Lee et al 1996a, b, c). In addition, Satt312 associated with salt tolerance (Lee et al 2004) was also found in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Satt515, Satt212 and Satt232 were three QTLs for CFC (Hyten et al 2004; Lee et al 1996a, b, c;Mansur et al 1993), Sat_289, Satt232 and Satt156 were three QTLs for PH (Lee et al 1996a, b, c;Mansur et al 1996;Lark et al 1995), Satt156 was the QTL for both CPC and PM (SoyBase81203828 and Lee et al 1996a, b, c). In addition, Satt312 associated with salt tolerance (Lee et al 2004) was also found in our study.…”
Section: Discussionsupporting
confidence: 71%
“…In the last decade, QTLs associated with salinity tolerance have been mapped in rice (Gong et al 1998;Koyama et al 2001;Lin et al 2004), wheat (Quarrie et al 2005;Ma et al 2007), tomato (Foolad 2001), and soybean (Lee et al 2004). In barley, diVerences in salinity tolerance including physiological and agronomical response have been reported, but few researches have been done in genetic analysis.…”
Section: Introductionmentioning
confidence: 98%
“…In the last decade, the development of molecular markers had made possible the genetic analysis of a number of complex traits, even to the extent of allowing the tagging of individual QTL (Yano and Sasaki 1997). Thus salt related QTL have been mapped in tomato (Foolad 2001;Foolad and Jones 1993), barley (Yoshiro and Kazuyoshi 1997), soybean (Lee et al 2004), Arabidopsis (Quesada et al 2002) and rice (Gong et al 1998;Gu et al 2000;Lin et al 1998Lin et al , 2004Zhang et al 1995). In wheat, there is a history of physiological research surrounding response to salinity stress, but genetic analysis is limited.…”
Section: Introductionmentioning
confidence: 99%